Anxiety and Academic Performance among Private Medical College Students (Journal of Current and Advance Medical Research, 2018)
Background: Medical students are in a huge pressure due to their academic syllabus. Objective: The purpose of the present study was to assess the relationship between anxiety and academic performance among private medical college.Methodology: This cross sectional study was done in private medical College Hospital, Dhaka, Bangladesh and 3rd and 4th year medical student were included. Data was   collected by using semi structured Socio-demographic questionnaire and Burn Anxiety Inventory scale and Checklist. Finally all data and results were analyzed using latest version of SPSS software. For descriptive statistics means, medians, SD and range will be calculated as required. Data will be presented in frequency table, bar, pie and scattered diagram as per need.  Statistical test chi-square test were used and p